Zoo U: A Stealth Approach to Social Skills Assessment in Schools. (22nd October 2012) - DeRosier, Melissa E.; Craig, Ashley B.; Sanchez, Rebecca P.
Abstract : This paper describes the design and evaluation of Zoo U, a novel computer game to assess children's social skills development. Zoo U is an innovative product that combines theory-driven content and customized game mechanics. The game-like play creates the opportunity for stealth assessment, in which dynamic evidence of social skills is collected in real time and players' choices during gameplay provide the needed data. To ensure the development of an engaging and valid game, we utilized an iterative data-driven validation process in which the game was created, tested, revised based on student performance and feedback, and retested until game play was statistically matched to independent ratings of social skills. We first investigated whether the data collected through extensive logging of student actions provided information that could be used to improve the assessment. We found that detailed game logs of socially relevant player behavior combined with external measures of player social skills provided an efficient vector to incrementally improve the accuracy of the embedded assessments. Next, we investigated whether the game performance correlated with teachers' assessments of students' social skills competencies. An evaluation of the final game showed (a) significant correlations between in-game social skills assessments and independently obtained standard psychological assessments of the same students and (b) high levels of engagement and likeability for students. These findings support the use of the interactive and engaging computer game format for the stealth assessment of children's social skills. The created innovative design methodologies should prove useful in the design and improvement of computer games in education.